PENGARUH MODEL PROJECT BASED LEARNING (PjBL) TERHADAP HASIL BELAJAR IPA MATERI HARMONI DALAM EKOSISTEM PADA KELAS V SD NEGERI 93 AMBON: Indonesia - Kouwe, Rasni; Rumahlatu, Dominggus; Pelamonia, Johanes (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the project-based learning model on students' learning outcomes in science on the subject of ecosystem harmony in grade V at SD Negeri 93 Ambon. The type of research used is quantitative with a quasi-experimental method and a pretest-posttest control group design. The results of the study indicate that there is a significant effect on student learning outcomes between the group taught using the Project-Based Learning (PjBL) model and the group taught using the lecture method in science lessons on the subject of harmony in ecosystems.